INTEGRASI TEAMWORK DAN KOHESIVITAS KELOMPOK DALAM PROSES PEMBELAJARAN PESERTA DIDIK PADA PENDIDIKAN JARAK JAUH ONLINE - Suyantiningsih, Suyantiningsih (MAJALAH ILMIAH PEMBELAJARAN, 2009)
This article examines computer-supported collaborative learning. It focuses on thestudents in an online program where an orientation toward teamwork and thedevelopment of group cohesiveness affect overall student learning and the learningthat results specifically from team interactions (team-source learning). Someresearches indicate that both teamwork orientation and group cohesiveness predictstudent learning, with group cohesiveness mediating the relationship betweenteamwork orientation and student learning. Teamwork orientation and groupcohesiveness appear to be equally important predictors of team source learning.